Ethics and ethical dilemmas: some implications for psychologists - Restrepo Botero, Juan Carlos (Poiésis, 2009)
When we ask people what they understand by ethics, many definitions and concepts are mentioned. Usually, people use the word moral as a synonym, they associate it with the things people can or cannot do, the right thing, what is allowed or forbidden, what society wants people to do, laws to follow (called “ethical code”) and so on. Are these ideas right?